Estimation of Productivity and Efficiency of Cotton Farmers in Pakistan: A Case Study of District Dera Ghazi Khan - Hameed, Abdul (Economic Journal of Nepal, 2013)
This paper investigates technical, allocative and economic efficiency of cotton farmers of district Dera Ghazi Khan using data envelopment analysis technique. Structured questionnaire is used to collect the data of cotton farmers. Data collection is carried out for Kharif season of 2012. A stratified random sampling selection technique was used to collect the data. The results reveal that mean total technical, pure technical, allocative, economic and scale efficiencies are 0.67, 0.94, 0.57, 0.54 and 0.71 respectively. It also shows that cotton farmer can produce average 22.5 mounds per acre seed cotton without reducing the inputs and technology. It also concludes that education, experience and contact with extension workers are significant determinants of technical efficiency of the cotton farmers.